Reply to Comment by J. Szilagyi and R. Crago on "Derivation of a Sigmoid Generalized Complementary Function for Evaporation With Physical Constraints". Issue 2 (21st February 2019) - Han, Songjun; Tian, Fuqiang
Abstract: Szilagyi and Crago criticized our sigmoid generalized complementary function from the boundary conditions and physical limits under the completely wet environments. We believe that their comments originate from different perspectives on the generalized complementary principle. In this reply, we clarify our perspectives, and explain our boundary conditions and physical constraints under the completely wet environments. Key Points: The sigmoid function adopts a complementary principle without involving potential evaporation under wet environments Boundary conditions under completely wet environments can be understood with the help of varying Priestley‐Taylor coefficient The EPT limit can be satisfied after introducing certain constraints on the parameters